Modified Radial Incision Technique in Reduction Nipple Hypertrophy - Marita, Adinda; Budiman, Budiman (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: Nipple hypertrophy causes psychosocial embarrassment and discomfort to the affected individuals. The only mean to correct it is by performing surgical procedure aiming to reduce the diameter as well as the vertical height of the nipple while preserving the lactiferous ducts. Patients and Methods: Two cases of nipple hypertrophy were described in this case series : the first one was a male patient presented with an overly prominent nipple of the left breast. Second case was a female patient with bilateral nipple hypertrophy. Circular design was performed at the tip of the nipple to match the size of the normal nipple. Three wedged excisions was made, and also three radial pillars with its pedicle divided into two parts: the lower part was de-epithelialized. This technique was able to reduce the diameter and also the vertical height of nipples without compromising their vascular supply. Result: No complications such as nipple necrosis or sensory loss were found in both patients during follow-up period. The normal symmetry of the nipple contour was restored. Conclusion: We described a simple technique for both male and female patients with nipple hypertrophy, which provided good aesthetic result and patient satisfaction.